Evaluation of cysts and odontogenic tumors over a period of 8 years in a reference medical hospital in Brazil (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the relative prevalence, demographic distribution and clinical-pathological characteristics of the maxillary odontogenics cysts and tumors of the jaws in a pathology laboratory located in a university hospital in Northeastern Brazil. Methods: An observational and retrospective study was carried out, in which information was collected on histopathological diagnosis, age, gender and location of the lesion of patients who had been diagnosed with odontogenic cysts or odontogenic tumors between 2013 and 2020.  Results: Among the 546 specimens, 57 were odontogenic cysts and 41 were odontogenic tumors. The most frequent odontogenic cysts were the odontogenic keratocyst 21 (21.4%) and the root cyst 19 (19.4%). The most frequent odontogenic tumors were ameloblastoma 27 (27.6%) and odontoma 6 (6.1%). Conclusion: The data found in this study are possibly associated with the service assistance profile.